Subjective Theories on Parental Discipline: A Perspective of Social Workers and Psychologists - Herrera-Durán, Francisco (2021)
Objective. To reconstruct the subjective theories of social workers and psychologists regarding parental discipline. Method. The following research is qualitative, and it was carried out through a descriptive type of design. Individual interviews were conducted to seven social workers and seven psychologists from the fourth region of Chile. The analysis of the collected data was performed through the grounded theory using encodings from the ATLAS.ti. software. Results. It is shown that the pieces of advice regarding parental discipline are strongly influenced by the professional training, the working experience, and some personal elements and conceptions of the interviewed professionals. Some differences are observed regarding the pieces of advice provided from both professional perspectives.